LANGUAGE CHANGE AND CYBERSPACE - Ika Nurhayani (ISSN)
Language is dynamic and therefore keeps on changing gradually. The main cause of language change is the need of human as social being to communicate and relate with others. The contact between human and their languages then leads to language change. Nowadays, human contact has never been easier and faster with the emergence of the Internet. The nature of online communication which differs from other forms of communication has certainly affected language change. This paper discusses language change in general and language change influenced by the cyberspace. In general, language first changes in phonetic and then followed by morpho–syntax. Language in cyberspace has distinct characteristics such as text–mediated, quick and efficient, English dominated, and orthographically innovative using abbreviations, numbers and pictures. In the future, languages of the world will be highly affected by English and the nature of text-mediated communication in cyberspace.